Gender dynamics in IVF: uncovering male and female factors for IVF at a tertiary care hospital - Naredi, Nikita; Prajapati, Vipin Kumar; Agrawal, Antara; lele, Prasad R.; Sahoo, Ipsita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: In spite of the global burden of subfertility affecting 8 to 12% of reproductive aged couples worldwide, not all sub fertile couples require in vitro fertilization (IVF). The decision to pursue IVF is typically based on a thorough assessment of the couple’s fertility challenges. Initially developed as a way to bypass irreparable tubal disease, IVF is now widely applied for treatment of infertility due to a variety of other causes. Latest achievements in the field of assisted reproduction have led to a rapid expansion in the indications of IVF. The objective of the study is to ascertain the various indications for which IVF was offered in the ART Centre of a public sector hospital, where such facilities are offered free of cost. Methods: This cross-sectional retrospective study was carried out over a period of 3 years in a tertiary care public sector hospital. Medical records including the infertility data of 1934 couples who underwent IVF cycles during the study period was analysed. Results: Of the 1934 couples taken up for IVF, 379 (19.6%) couples were for male factor only, 14.7% underwent IVF for chronic anovulation and 478 (24.7%) couples underwent IVF for combined male and female factors while 14.6% for idiopathic infertility. Conclusions: Both male and female factors contribute vividly to the burden of infertility and result in IVF to attain a successful pregnancy. In our study combined factors was the commonest indication for IVF.